The Epistemic Ambitions of the Criminal Trial: Truth, Proof, and Rights - Sarah Jane Summers (Quaestio Facti)
This paper sets out to examine the epistemic ambitions of the criminal trial. It argues for an understanding of criminal evidence and proof which is inextricably connected to the demands of justified punishment and fair trials in the rule of law. Criminal trials must prioritise the individual rights of the accused, but they also define more generally the manner in which those subject to the law are to be treated in order to engender public acceptance of the verdict. In this sense, it is sceptical of instrumental accounts of criminal adjudication and, in particular, of the feasibility of any sort of separation of outcome and process. It subscribes instead to the notion that (true) belief in the necessity of imposing punishment in the rule of law will only be warranted if it is based on appropriate reasons, understood as reasons which are formed following a distinct type of process.